Fosfito de potássio não protege plantas de milho contra os efeitos fitotóxicos do glyphosate - Gomes, Giovanna Larissa Gimenes Cotrick [UNESP]; Velini, Edivaldo Domingues [UNESP]; Carbonari, Caio Antonio [UNESP] (My University, 2015)
There are conflicting reports on the effect of potassium phosphite with or without glyphosate in plants. Some of them indicate that potassium phosphite may cause injuries when applied alone, while others point out that it can reduce the injury caused by glyphosate, when applied in association with this herbicide. This study aimed at evaluating the effect of potassium phosphite alone or in association with glyphosate on visual injury, dry matter accumulation, phytotoxicity indicator compounds levels and aromatic amino acid contents in maize plants. Treatments consisted of isolated or associated application of two glyphosate doses (72 g ha-1 and 720 g ha-1) and one potassium phosphite dose (Fosway - 3 L ha-1). The visual evaluations of injury and harvesting were performed at 2, 4, 10 and 15 days after application. The potassium phosphite applied alone did not cause injury to plants, and its association with glyphosate, regardless of the dose tested, did not protect the plants against the injury and dry mass reduction caused by the herbicide. There was an accumulation of shikimic and quinic acids on the plants subjected to the highest dose of glyphosate with or without phosphite. The potassium phosphite treatments with or without glyphosate showed higher tryptophan levels and did not alter the phenylalanine and tyrosine contents in the plants.
Potassium phosphite does not protect maize plants against the phytotoxic effects of glyphosate
Keywords: Aromatic amino acids; Quinic acid; Shikimic acid; Zea mays